Vitamin D Supplementation Efficacy in Severe Vitamin D-Deficient versus Insufficient COPD Patients: A Stratified Meta-Analysis of Exacerbation Risk - Ikhsan Tri Kurnia; Dewi Wijaya (HM Publisher, 2026)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by persistent airway inflammation and recurrent exacerbations that accelerate disease progression. Vitamin D deficiency is highly prevalent in this population and correlates with impaired macrophage function. However, randomized controlled trials regarding supplementation have yielded conflicting results. We hypothesized that efficacy is limited by a ceiling effect, where benefits are strictly restricted to patients with profound baseline deficiency. Methods: We conducted a systematic review and stratified meta-analysis of randomized controlled trials comparing Vitamin D supplementation to placebo in COPD. To ensure methodological homogeneity and avoid data duplication, we strictly included only primary RCTs and excluded aggregate IPD meta-analyses. Studies investigating acute treatment of active exacerbations were also excluded. Data were stratified by baseline serum 25-hydroxyvitamin D [25(OH)D] levels into Severe Deficiency (<10 ng/mL) versus Insufficiency/Sufficiency (≥10 ng/mL). The primary outcome was the risk of moderate-to-severe exacerbations, analyzed using pooled Odds Ratios (OR) with a random-effects model. Results: Five pivotal prevention trials (Lehouck, PRECOVID, ViDA, Hornikx, and Rafiq Pilot) comprising approximately 1,212 participants were included in the quantitative synthesis. In the unstratified analysis, Vitamin D showed no significant benefit (OR 0.78; 95% CI 0.55–1.10). However, stratification revealed a distinct therapeutic window. Patients with severe deficiency (<10 ng/mL) experienced a statistically significant reduction in exacerbation risk (Pooled OR 0.51; 95% CI 0.32–0.87; p=0.012). This effect was driven primarily by trials utilizing high-dose bolus supplementation. Conversely, patients with baseline levels ≥10 ng/mL showed no benefit (OR 0.98; p=0.72), confirming the biological ceiling effect. Conclusion: Vitamin D supplementation confers a significant protective benefit against COPD exacerbations exclusively in patients with severe baseline deficiency (<10 ng/mL). The results support a precision medicine approach—screen, stratify, and target—while cautioning that efficacy appears dependent on correcting profound deficiency, potentially utilizing high-dose intermittent regimens.